Galantamine for the treatment of BPSD in Thai patients with possible Alzheimer's disease with or without cerebrovascular disease - S. Tangwongchai (2018)
Objectives. This study was to investigate an efficacy of galantamine in treatment of behavioral and psychological symptoms of dementia in Thai elderly who suffered from possible Alzheimer's disease (AD) with or without cerebrovascular disease and vascular dementia. Methods. A 6-month, multicenter, open-label, uncontrolled trial was undertaken in 75 patients. Eligible patients received an initial galantamine dose of 8 mg/dayand escalated over 5 to 8 weeks to maintenance doses of 16 or 24 mg/day. The behavioral response was assessed as an intention-to-treat analysis using the Behavioral Pathology in Alzheimer's Disease Rating Scale (BEHAVE-AD). Results. Galantamine improved behavioral and psychological symptoms of dementia (P <.05 vs baseline) over the 24 weeks of treatment. BEHAVE-AD score was significantly improved from baseline in paranoid and delusion ideation, diurnal rhythm disturbances, anxieties, and phobias. Conclusions. Galantamine may be a well-tolerated and effective treatment option for improving psychotic, behavioral, and psychological symptoms in Thai elderly with possible AD with or without cerebrovascular disease and vascular dementia. © 2009 Sage Publications.